H1N1 INFLUENZA VERSUS SEASONAL INFLUENZA MORBIDITY AND MORTALITY: A PROSPECTIVE STUDY IN AL-KINDY TEACHING HOSPITAL/ IRAQ-BAGHDAD - AL-Ameri, Ismail A. Hussain; Fadel, Baker; Sajid, Ali; Kareem, Imad (AL-Kindy College Medical Journal, 2016)
Background: H1N1 influenza pandemic or swine flu was an influenza pandemic first described in Iraq in October 2009 .The virus appeared to be anew strain of H1N1 causes wide range of morbidity and mortality among different genders and age groups as part of worldwide pandemics.Seasonal flu is a contagious respiratory illness caused by influenza viruses that infect the nose, throat, and lungs. It can cause mild to severe illness, and at times can lead to death. The best way to prevent the flu is by getting a flu vaccine each year.Objectives: Is to determine the morbidity and mortality in different age groups in patients with H1N1 influenza versus those patients with seasonal influenza who were admitted at the same time to AL-kindy teaching hospital during pandemic 2009. Type of the study: A retrospective observational study.Methods: A total number of 210 cases with influenza symptoms and signs were included in this study which was conducted at AL-kindy teaching hospital , Baghdad, Iraq at inpatient medical wards over a period from October to December 2009. All cases were tested by real time PCR for H1N1 influenza virus by taking nasal and throat swab in addition to monitoring symptoms and signs of influenza and chest radiographs.Results: Out of 210 cases, 90 (42.85%) cases were positive for H1N1 influenza and 120 (57.14%) cases had negative test are considered having seasonal influenza. Of the positive cases(64.44%) were males and (35.55%) were females. Of negative cases(seasonal flu)male gender were (61.66%) , while female gender were (38.33%). 57.77% of positive cases developed flue like illness compared with 54.16% of negative while 25.55% of positive developed pneumonia compared with 22.5% of negative.5.55% of positive cases developed ARDS compared with 5% only in negative cases.11.11% had different presentation in positive cases (bronchitis ,gastroenteritis) while 18.33%of negative. Mortality in positive cases are 14.4% compared with only 10% in negative cases.Conclusions: Influenza A/H1N1had same symptoms and signs of epidemic seasonal influenza but run aggressive and short course of morbidity in 3-5 days with high percentage of complication and high mortality compared with seasonal epidemic influenza with rare affection above 65 years old, both groups had same incidence of complication with pneumonia and ARDS